A multiple-node hormone regulation of neuroendocrine-PID (MnHR-NEPID) control for nonlinear MIMO systems - Mohd Riduwan, Ghazali; Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail (Taylor & Francis, 2020)
This paper proposed a multiple-node hormone regulation neuroendocrine-proportional-integration-differential (MnHR-NEPID) controller based on adaptive safe experimentation Dynamics (ASED) for nonlinear multi-input-multi-output (MIMO) systems. In the existing neuroendocrine-PID (NEPID) controller of the single-input-single-output (SISO) system, only a single node of hormone regulation is used due to a single control variable. Meanwhile, in the MIMO system, since having many control variables, it is worth introducing an MnHR-NEPID for better controller performance by prioritizing each node’s control regulation from their level of error. In particular, instead of considering its own hormone regulation, each node’s hormone regulation is also generated based on the change of error from other control variables or nodes if the error of that corresponding control variable exceeds the given error threshold. Here, the relation between hormone regulation and the change of error is adopted based on the normalized Gaussian function. As a result, better prioritize control regulation with heightened control accuracy can be subsequently achieved due to interactions between multiple nodes of hormones available for the nonlinear MIMO system. The performance error and control input for several nonlinear MIMO systems were further tracked to assess the proposed controller’s performance. Standard PID, NEPID, and sigmoid-based secretion rate neuroendocrine-PID (SbSR-NEPID) controllers were also compared. Thus, this simulation work has acknowledged higher accuracy within the design of an MnHR-NEPID controller, with comparatively superior objective function and total norm of error resulted in better control performance.